Liquid supported maxillary complete denture: A case report (Indian Journal of Case Reports, 2020)
Patients with problematic situations like flabby tissues, diabetes, xerostomia, atrophied ridges, parafunctional habits, etc. pose significant problems in attaining basic objectives of getting a stable and retentive dental prosthesis. In the literature, several techniques have been mentioned, each having their own advantages and disadvantages, to achieve continued adaptation of dental prosthesis to the mucosa both at resting and functional state in such situations. This article presents a case report describing a technique of fabricating a liquid supported maxillary complete denture in which the characteristics of pliability and rigidity can be combined to achieve the objectives of proper retention, stability, support and comfort to the patient.